Video Profile Balai Latihan Kerja Pada Dinas Ketenagakerjaan Kota Tangerang - Sunarya, Lusyani; Abdurachman, Bisma; Ningsih, Putri Rahayu (Technomedia Journal, 2021)
ABSTRACT Technology now makes the world of work like companies, other agencies looking for new and quality human resources in the world of work. The Manpower Office helps workers who have just graduated or who want to have skills through training organized by the Tangerang City Manpower Office, which is located on Jalan Perintis Kemerdekaan II No.1, Cikokol, Babakan, Tangerang, Kec. Tangerang, Kota Tangerang, Banten. Problems faced Training Center, namely, the lack of media in disseminating information, training seminars given BLK, so the need for the media to convey information in an interactive and engaging. The purpose of this research is to SDM workers who are ready to compete or who are ready to enter the world of work. Benefits that can be tasted Tangerang urban community that is easy to obtain profile information Manpower, Training Center as a training ground. The research methods are: data, SWOT analysis, media design and media concepts, namely: pre-production, production, and post-production. The results of this study are in the form of a video profile media which is expected to help support information for the Tangerang City Manpower Office and improve the ability of Tangerang City Human Resources. Keywords - Video Profiles, Information, Human Resources